Identifikasi Faktor yang Mempengaruhi Efektivitas Kinerja Aparatur Sipil Negara dalam Pelayanan Publik - Batubara, Soulthan Saladin; Insan, Muhammad Yalzamul; Puasari, Sherlyna (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The purpose of this study is to find out and test the variables of supervision (X1), motivation (X2), and work discipline (X3) on the effectiveness of the performance (Y) of the State Civil Apparatus at the Social Service, Women's Empowerment, and Child Protection of Batu Bara Regency. This study uses an associative type of research. The population of this study is all state civil servants who have the status of State Civil Apparatus in the Social Service, Women's Empowerment, and Child Protection in Batu Bara Regency, which totals 48 people. The variables of this study include the variables of supervision, motivation, work discipline, and performance. The data collection technique used to measure all the variables studied is a questionnaire. Data analysis was carried out quantitatively using descriptive statistics and t-test, F-test, and determination coefficient test. The results of the study showed that the factors of supervision, motivation, and work discipline partially and simultaneously had a positive and significant effect on the performance of civil servants in the Social Service of Women's Empowerment and Child Protection of Batu Bara Regency. Most of the performance is influenced and achieved through work motivation, supervision, and work discipline, while the rest is influenced by other factors. The work motivation variable has the greatest influence on employee performance with a calculated value of 3. 382